A System of Geomorphological Mapping for Western Rajasthan with Relevance for Agricultural Land Use - Moharana, P C; Gaur, Mahesh Kumar; Choudhary, Chanchal; Chauhan, J S; Rapurohit, R S (Annals of Arid Zone, 2016)
A geomorphological map of arid western Rajasthan has been prepared using a recently developed classification system for national mapping in India at 1:50,000 scale. The mapping involved digital interpretation of the false colour composite (FCC) of images of 2005-06 from LISS-III scanner in the Indian Remote Sensing Satellite (IRS), followed by field verification of the mapped units and analysis of sediments from key sites. It resulted in the generation of three-tier mapped information on the origin, processes and landform units, as well as other digital database on landform characteristics. To find out the agricultural use of the landforms, a land use map of the same area for 2005-06 was draped on the derived map of landforms, using GIS. Area statistics for all the maps was generated for each of the four agro-climatic zones in western Rajasthan. The mapping reveal that landforms of aeolian origin cover the maximum area (~79%), which dominantly consist of sand dunes (~50%). Landforms of fluvial origin have been masked over large area by the aeolian features, leaving only 13% area as visible. Croplands occur on all the major landforms, but irrigated croplands occur dominantly on older alluvial plains. Sand dunes and sandy plains are dominantly under un-irrigated croplands, and partly under irrigated croplands, which may increase the risk of sand mobility. These and other results have been discussed in the paper. Key words: Geomorphology, mapping, agricultural land use, western Rajasthan, ACZ, GIS.